Pengaruh Model Project Based Learning Berbantuan Media Virtual Terhadap Kreativitas Fisika Peserta Didik - Ni Made Yeni Suranti; Gunawan Gunawan; Hairunnisyah Sahidu; Ahmad Harjono (Indonesian Journal of Applied Science and Technology, 2021)
This study aims to examine the effect of the Project-Based Learning (PjBL) model assisted by virtual media on students' physics creativity. This quasi-experimental research applied an untreated control group design with a pretest and posttest. The research sample was selected using a purposive sampling technique, consisting of 34 students in the experimental class and 33 students in the control class at SMAN 2 Mataram. The data collection instrument was a physics creativity test comprising 5 verbal and 3 figural items. Data were analyzed using a polled variance t-test after fulfilling the homogeneity and normality prerequisite tests. The results showed that >  (4.95 > 2.00), meaning was rejected and  was accepted. This study concludes that the Project-Based Learning model assisted by virtual media has a significantly positive effect on students' physics creativity. The increase in creativity in the experimental class was higher than in the control class, with verbal creativity improvement being more optimal than figural creativity in both classes. Teachers are advised to manage time efficiently and ensure students' operational readiness regarding virtual media.